Chronic subdural hematoma that may be caused by nephrotic syndrome: a case report and literature review - Xue, Hang; Xue, Kun; Wang, Xiaohui; Xu, Weidong; Zhang, Weitao; Xia, Guangwen (Frontiers in Neurology, 2024)
Background Chronic subdural hematoma (CSDH) is a common complication of neurosurgery. Craniocerebral trauma is the likely cause. There are no reports relating CSDH with nephrotic syndrome. Its pathogenesis is very rare, and there are no previous reports on treatments for this disease. We report a case of chronic subdural hematoma that may be caused by nephrotic syndrome and review the previous literature on this subject. Case summary We report a rare case of chronic subdural hematoma that may be caused by nephrotic syndrome. After the patient was admitted to the hospital, relevant laboratory tests were conducted, and a large amount of protein was detected in the patient’s urine, indicating hypoproteinaemia and hyperlipidemia. The patient was diagnosed with nephrotic syndrome. After the exclusion of related surgical contraindications, the patient underwent trepanation and drainage of the chronic subdural hematoma. Subsequent treatment with oral atorvastatin was provided after surgery. The patient was transferred to the nephrology department for further treatment of nephrotic syndrome if his neurological condition improved. No neurological sequelae were detected at the follow-up visit 3 months after the operation. Conclusion Chronic subdural hematomas are rarely caused by nephrotic syndrome. Trepanation and drainage may be considered for patients confirmed to have adequate hematoma liquefaction on imaging and who can tolerate craniotomy. Atorvastatin should be supplemented as prophylactic treatment after the operation. Nephrotic syndrome should be treated as soon as the patient’s neurological condition is stable.